Project Financing of German Universities as an Instrument for Improving their Competitiveness among the World's Leading Scientific and Educational Centers - Grishina, Olga Alekseevna (2021)
Higher education institutions present key social institutions ensuring the creation and transfer of knowledge, intellectual capital, and innovations. This fact determines the significance of universities in state regulation and allocating financial resources to the best of them is becoming a crucial objective in many countries. Goals of the article is to study of the German Excellence Initiative project. The study identifies the characteristics of the Excellence Initiative project. A set of indicators of the project effectiveness is presented and the positive effects and problems of the project are indicated. Directions for the development of the European Universities’ project financing system are proposed. Project financing allowed changing the organizational structure of the German science system. However, it is necessary to continue the search for various cooperation formats and the ways for the development of gifted researchers in the scientific sphere, strengthen the universities’ prestige and infrastructure, and further improve the project financing models. Institutional strategies are aimed at strengthening the positions of a university overall allowing it to successfully compete with the leading participants in the international scientific arena. An institutional strategy requires a university to develop a long-term policy of consistent expansion and improvement of the quality of its research and promotion of young scientists and researchers allowing to identify the existing strengths and set priorities.